A carbon dot-based tandem luminescent solar concentrator. Issue 12 (21st February 2020) - Zdražil, Lukáš; Kalytchuk, Sergii; Holá, Kateřina; Petr, Martin; Zmeškal, Oldřich; Kment, Štěpán; Rogach, Andrey L.; Zbořil, Radek
Abstract : We report a large area tandem LSC that is based exclusively on carbon dots and exhibits η int of 23.6% and η ext of 2.3%. Abstract : Luminescent solar concentrators (LSCs) are light-management devices and are used for harvesting and concentrating solar light from a large area to their edges. Being semitransparent devices, LSCs show great promise for future utilization in glass walls of urban buildings as environmentally friendly photovoltaic power plants. The development of cheap and eco-safe materials, the extension of the LSC operation range, and the enhancement of the optical efficiency are the key challenges, which need to be solved in order to transform energetically passive buildings into self-sustainable units. Herein, a large area (64 cm 2 ) tandem LSC fabricated using entirely eco-friendly highly emissive blue, green, and red carbon dots is demonstrated, with an internal optical quantum efficiency of 23.6% and an external optical quantum efficiency of 2.3%, while maintaining a high transparency across the visible spectrum. This opens up a new direction for the application of carbon dots in advanced solar light harvesting technologies.